Noise and detectivity limits in organic shortwave infrared photodiodes with low disorder - Zhenghui Wu (Nature Portfolio, 2020)
Abstract To achieve high detectivity in infrared detectors, it is critical to reduce the device noise. However, for non-crystalline semiconductors, an essential framework is missing to understand and predict the effects of disorder on the dark current. This report presents experimental and modeling studies on the noise current in exemplar organic bulk heterojunction photodiodes, with 10 donor–acceptor combinations spanning wavelength between 800 and 1600 nm. A significant reduction of the noise and higher detectivity were found in devices using non-fullerene acceptors (NFAs) in comparison to those using fullerene derivatives. The low noise in NFA blends was attributed to a sharp drop off in the distribution of bandtail states, as revealed by variable-temperature density-of-states measurements. Taking disorder into account, we developed a general physical model to explain the dependence of thermal noise on the effective bandgap and bandtail spread. The model provides theoretical targets for the maximum detectivity that can be obtained at different detection wavelengths in inherently disordered infrared photodiodes.